2019
DOI: 10.1093/advances/nmy108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Canola Oil on Body Weight and Composition: A Systematic Review and Meta-Analysis of Randomized Controlled Clinical Trials

Abstract: A number of clinical trials have examined the effect of canola oil (CO) on body composition in recent years; however, the results have been inconsistent. The present investigation aims to examine the effect of CO on body weight (BW) and body composition using a systematic review and meta-analysis of controlled clinical trials. Online databases including PubMed, Scopus, and Google Scholar were searched up to February, 2018 for randomized controlled clinical trials that examined the effect of CO on anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 106 publications
1
11
1
Order By: Relevance
“…However, android to gynoid ratio was increased within high-oleic canola oil with flaxseed oil period compared to high-oleic canola oil. By contrast to our findings, a recent metaanalysis, 43 revealed that CO consumption results in a slight decrease in body weight (approximately 0.3 kg); however, CO consumption did not change other body composition indices. The majority of studies included in that meta-analysis prescribed specific amounts of CO in the context of high-CO diets or CO was supplemented in the context of foods.…”
Section: Discussioncontrasting
confidence: 99%
“…However, android to gynoid ratio was increased within high-oleic canola oil with flaxseed oil period compared to high-oleic canola oil. By contrast to our findings, a recent metaanalysis, 43 revealed that CO consumption results in a slight decrease in body weight (approximately 0.3 kg); however, CO consumption did not change other body composition indices. The majority of studies included in that meta-analysis prescribed specific amounts of CO in the context of high-CO diets or CO was supplemented in the context of foods.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, high phenolic olive oil may improve some cardiovascular risk factors stronger than refined olive oil [82, 83]. Higher consumption of canola oil results in a modest decrease in BW, whereas no significant effect was observed on other adiposity measures [84].…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean diet is characterized by high consumption of olive oil, with high amount of MUFA 185,186 . This diet has a potential beneficial effect on CVDs, cancer, hyperlipidemia, and fatty liver 187 . It is suggested that several health benefits of Mediterranean diet including improvement of cardiovascular risk factors, such as lipid profile, blood pressure, postprandial hyperlipidemia, endothelial dysfunction, oxidative stress, and antithrombotic effects are due to high amounts of olive oil 188 .…”
Section: Vegetable Oilsmentioning
confidence: 99%
“…185,186 This diet has a potential beneficial effect on CVDs, cancer, hyperlipidemia, and fatty liver. 187 It is suggested that several health benefits of Mediterranean diet including improvement of cardiovascular risk factors, such as lipid profile, blood pressure, postprandial hyperlipidemia, endothelial dysfunction, oxidative stress, and antithrombotic effects are due to high amounts of olive oil. 188 In some randomized clinical trials, it has been shown that olive oil has beneficial effects on blood lipids.…”
Section: Vegetable Oilsmentioning
confidence: 99%